Lazarus syndrome in nonsmall cell lung cancer patients with poor performance status and major leukocytosis following nivolumab treatment. Issue 1 (27th July 2017) - Pluvy, Johan; Brosseau, Solenn; Naltet, Charles; Opsomer, Marie-Agnès; Cazes, Aurélie; Danel, Claire; Khalil, Antoine; Zalcman, Gérard; Gounant, Valerie
Nivolumab appears efficacious in highly PD-L1-expressing NSCLC with poor PS, resulting in Lazarus syndrome http://ow.ly/X92e30coTsB